Fergana Valley During the Time of Bukhara Khan Imam Quli Khan Political Processes - Bahridinovich, Musaev Azizbek (Researchparks Publishing, 2023)
This article discusses the political life in the Ferghana Valley during the reign of the strongest representative of the Ashtarkhanids, Imam Qulikhan, and the place of the region in relations with neighboring settlers.